Documenting mycotoxins - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
A reference library is currently being established by UNEP in Nairobi to help African countries control mycotoxins and to take preventative measures for the future. It will bring together all the literature that has been published on this subject....